ARTS EDUCATION'S VIEW ON ARTISTIC RESEARCH - Zakarias Aria Widyatama Putra; Aline Rizky Oktaviari Satrianingsih; Renistiara Medilianasari; Brian Trinanda Kusuma Adi (Jurnal Scientia, 2023)
The direction of arts education in learning and learning activities produces outcomes of sense of taste, creativity, aesthetic growth, and cultivation in the arts, as well as behavior (etiquette), social sense, and conscious culture in everyday life. This research places the view of arts education on artistic research and its appropriation, and the purpose of the research is to compare the views of the research domain in arts education and artistic research. In order to reveal the subject's views, this research uses a qualitative method with this type of literature study. The data disclosure is based on literature data, notes on research materials, and unstructured interviews with research methodologists. The systematics to reveal the data are realized through the analysis process, starting with the data condensation, data depiction, data presentation, and conclusion drawing. The result obtained is that the view of arts education towards artistic research can be used as needed. This means that the denotation of education is broken down in artistic research, which has an emphasis on the arts. Artistic research is one of the scientific methods that academics and arts practitioners can use to prove that the creation of works of art is one of the results of scientific thinking that can have an impact on the knowledge and skills of students in arts education.